Development of neffy, an Epinephrine Nasal Spray, for Severe Allergic Reactions - Anne K. Ellis; Thomas B. Casale; Michael Kaliner; John Oppenheimer; Jonathan M. Spergel; David M. Fleischer; David Bernstein; Carlos A. Camargo; Richard Lowenthal; Sarina Tanimoto (MDPI AG, 2024)
Epinephrine autoinjectors (EAIs) are used for the treatment of severe allergic reactions in a community setting; however, their utility is limited by low prescription fulfillment rates, failure to carry, and failure to use due to fear of needles. Given that delayed administration of epinephrine is associated with increased morbidity/mortality, there has been a growing interest in developing needle-free, easy-to-use delivery devices. neffy (epinephrine nasal spray) consists of three Food and Drug Administration (FDA)-approved components: epinephrine, Intravail A3 (absorption enhancer), and a Unit Dose Spray (UDS). neffy's development pathway was established in conjunction with the FDA and the European Medicines Agency and included multiple clinical trials to evaluate pharmacokinetic and pharmacodynamic responses under a variety of conditions, such as self-administration and allergic and infectious rhinitis, as well as an animal anaphylaxis model of severe hypotension, where neffy demonstrated a pharmacokinetic profile that is within the range of approved injection products and a pharmacodynamic response that is as good or better than injections. The increased pulse rate (PR) and blood pressure (BP) observed even one minute following the administration of neffy confirm the activation of α and β adrenergic receptors, which are the key components of epinephrine's mechanism of action. The results suggest that neffy will provide a safe and effective needle-free option for the treatment of severe allergic reactions, including anaphylaxis.